Life Cycle Assessment and Material Flow Analysis Research on Electronic Waste in Asia: Trends, Gaps, and Insights - Septiariva, Iva Yenis; Suhardono, Sapta (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
The term "electronic waste" or "e-waste" refers to a broad array of discarded electronic products and electrical appliances that have reached the end of their useful lives. These include computers, smartphones, televisions, and refrigerators. Over the past three years, the volume of e-waste has surged, from 24.9 million metric tons (MMT) in 2019 to 33 MMT in 2022, as reported by the United Nations in The Global E-Waste Monitor 2024. This increase is driven by the expansion of the electronics industry and the increased usage of electronic devices. Life Cycle Assessment (LCA) and Material Flow Analysis (MFA) are key methodologies used to assess the environmental impact and material flow of e-waste management, respectively. However, many MFAs fail to track the flow of secondary materials that are reused, recycled, and reduced in the new products. This study addresses these gaps by analyzing e-waste management trends in Asia using a systematic literature network analysis (SLNA). SLNA combines a systematic literature review (SLR) and bibliometric analysis (BA) to offer a comprehensive review from various perspectives. This study aims to identify underexplored topics and trends, provide insights that can shape future research directions, and inform government policies on e-waste management in Asia.